2020
DOI: 10.1016/j.celrep.2020.107534
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Small Ribosomal Subunits Reveals Modes and Regulation of Translation Initiation

Abstract: Highlights d RCP-seq allows the study of both scanning and translating ribosomal complexes d Threading of mRNA through the small ribosomal subunit loads the subunits onto the 5 0 UTR d Processivity of small ribosomal subunits is high while scanning 5 0 UTRs d Direct measurements of initiation redefine optimal start codon context

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 59 publications
7
32
0
Order By: Relevance
“…One of the reasons underlying this correlation lies in a higher potential of long 5 0 UTRs to create secondary RNA structures. Indeed, a mere extension of 5 0 UTR without introduction of secondary RNA structures does not significantly impact translation (Hinnebusch, 2011), which agrees with data suggesting comparable ribosome scanning efficiency on 5 0 UTRs of different lengths (Giess et al, 2020). The presence of secondary structures negatively correlates with TE of the respective mRNA in cells of multiple origins, from bacteria to humans (Araujo et al, 2012;Yus et al, 2017;Leppek et al, 2018;Li et al, 2019).…”
Section: The First Transcribed Nucleotide and The Cap Structuresupporting
confidence: 84%
See 3 more Smart Citations
“…One of the reasons underlying this correlation lies in a higher potential of long 5 0 UTRs to create secondary RNA structures. Indeed, a mere extension of 5 0 UTR without introduction of secondary RNA structures does not significantly impact translation (Hinnebusch, 2011), which agrees with data suggesting comparable ribosome scanning efficiency on 5 0 UTRs of different lengths (Giess et al, 2020). The presence of secondary structures negatively correlates with TE of the respective mRNA in cells of multiple origins, from bacteria to humans (Araujo et al, 2012;Yus et al, 2017;Leppek et al, 2018;Li et al, 2019).…”
Section: The First Transcribed Nucleotide and The Cap Structuresupporting
confidence: 84%
“…For instance, when MEF cells are starved for glucose, mRNAs bearing either A or G nucleotides at the cap-proximal residue recruit eIF4E more efficiently, promoting the initiation of their translation (Tamarkin-Ben-Harush et al, 2017). A recent genome-wide study of translation initiation in the developing zebrafish embryo reported similar observations, suggesting that mRNAs having cytosine at the +1 position, particularly those followed by the TOP motif (see below), exhibit less efficient 43S scanning (Giess et al, 2020). Collectively, these findings support the notion that the first transcribed nucleotide, stemming from either use of alternative promoters or as a part of clustered transcription initiation sites, is a critical determinant regulating the efficiency of mRNA translation.…”
Section: The First Transcribed Nucleotide and The Cap Structuresupporting
confidence: 61%
See 2 more Smart Citations
“…To this end, we employed 40S ribosome footprinting, which captures the positions of 40S ribosomes during scanning and recycling 47 . We and others recently adapted this method for animal cells 29,48,49 . This revealed that loss of DENR causes a strong accumulation of 40S recycling intermediates on stop codons of both main ORFs (mORFs) (Fig.…”
Section: Denrmentioning
confidence: 99%